Organic management increases beneficial microorganisms and promotes the stability of microecological networks in tea plantation soil - Huang, Xinhui; Zheng, Yuting; Li, Panfeng; Cui, Jixiao; Sui, Peng; Chen, Yuanquan; Gao, Wangsheng (Frontiers in Microbiology, 2023)
Introduction Organic agriculture is highly regarded by people for its commitment to health, ecology, care, and fairness. The soil microbial community responds quickly to environmental changes and is a good indicator for evaluating soil microecology. Therefore, from the perspective of soil microbial communities, elucidating the impact of organic management on soil microecology in tea plantations has great significance for improving local tea plantation systems. Methods The study collected bulk soil from organic management (OM) and conventional management (CM) tea plantations in Pu'er City, a major tea-producing area in China, and analyzed their species diversity, structural composition, and co-occurrence networks using metagenomics technology. Results Compared with CM, the diversity index (Shannon) and evenness index (Heip) of soil fungi increased by 7.38% and 84.2% in OM tea plantations, respectively. The relative abundance of microorganisms related to the nitrogen cycle increased. Specifically, there was a significant increase in Rhodobiales, a 2-fold increase in Nitrospirae, and approximately 1.95 and 2.03 times increases in unclassified genera within Betaproteobacteria and Deltaproteobacteria, respectively. The relative abundance of plant residue degradation species, Gemmatimonadetes, Ascomycota, and Basidiomycota, increased by 2.8, 1, and 1.4 times, respectively. The OM was conducive to the establishment of collaborative relationships among bacterial species and increased the diversity and complexity of species relationships in fungal communities. The network stability of soil ecosystems was promoted. The organic tea plantations' keystone taxa contained mycorrhizal fungi (Pezoloma_ericae, Rhizophagus_irregularis, Rhizophagus_clarus), as well as species involved in soil nitrogen metabolism (Acidobacteria_bacterium, Acidobacteriia_bacterium_AA117, Sphingomonas_sp._URHD0007, Enhydrobacter_aerosaccus), pathogen (Erysiphe_pulchra), and parasites (Paramycosporidium saccamoeba). The partial least squares method (PLS-SEM) indicated that OM affected N-NH4+ negatively, increasing the abundance of fungi, and thereby positively affecting the Shannon index. Conclusion In brief, reasonable organic management can improve the diversity of soil microorganisms, increase the relative abundance of beneficial bacteria in tea plantation soil, and promote the stability of the soil microbial ecological network.